PROBLEMATIKA PENDIDIKAN ISLAM DALAM RUMAH TANGGA DI DESA MORELLA KABUPATEN MALUKU TENGAH - Saida Manilet (al-Iltizam: Jurnal Pendidikan Agama Islam, 2020)
This study aims to reveal: 1) The form of Islamic education for children in households in Morella village, Central Maluku district, 2) Constraints and solutions adopted in the implementation of Islamic education in households in Morella village, Central Maluku Regency. This study uses a descriptive qualitative research method with a phenomenolological approach with data collection procedures, namely observations related to forms of Islamic education for children in the household, and interviews related to the obstacles found by parents in educating children with Islamic education and the solutions made. Data collection procedures are carried out by collecting data related to forms of Islamic education in the household, presenting data that is included in the focus of the study and making conclusions. The results found: 1) the form of Islamic education in the household includes faith education, including: a) Opening the life of a child with the sentence Laa Ilaaha Illallaah, by various ways of tending the child at birth, child technique, breastfeeding a child, cutting / shaving hair or aqiqah, circumcision, b) introduce halal and haram, and c) reading the Qur'an. Education in aspects of worship include: a) Teaching Salat, b) fast and c) give alms. Education in moral aspects includes: a) Prohibition of traveling and b) Behaving honestly. Education in social aspects: a) Do good to parents, b) Maintain friendship with relatives, c) Do good to neighbors, d) Respect for older people, e) Ethics of greeting, f) Ethics of eating and drinking, and g) Meet friend's invitation.